Genome variability of domestic tomato varieties: data from AFLP analysis - A. V. Kulakova; E. A. Dyachenko; A. V. Shchennikova; O. N. Pyshnaya; E. A. Dzhos (Вавиловский журнал генетики и селекции)
Tomato Solanum lycopersicum L. is one of the main vegetable crops, accessions and cultivars of which are characterized by a low level of genomic polymorphism. Introgressive tomato breeding uses related wild Solanum species to improve cultivars for stress tolerance and fruit quality traits. The aim of this work was to evaluate the genome variability of 59 cultivars and perspective breeding lines of S. lycopersicum and 11 wild tomato species using the AFLP method. According to the AFLP analysis, four combinations of primers E32/M59, E32/M57, E38/M57, and E41/M59, which had the highest PIC (polymorphism information content) values, were selected. In the process of genotyping a collection of 59 cultivars/lines of S. lycopersicum and 11 wild tomato accessions, the selected primers revealed 391 fragments ranging in size from 80 to 450 bp, of which 114 fragments turned out to be polymorphic and 25 were unique. Analysis of the amplification spectra placed wild tomato accessions into separate clades. Sister clades included cultivars of FSCV breeding resistant to drought and/or cold and, in part, to late blight, Alternaria, Septoria, tobacco mosaic virus and blossom end rot, as well as tomato accessions not characterized according to these traits, which suggests that they have resistance to stress factors. In accessions of distant clades, there was clustering on the basis of resistance to Verticillium, cladosporiosis, Fusarium, tobacco mosaic virus, gray rot, and blossom end rot. The combination of accessions according to their origin from the originating organization was shown. The primer combinations E32/M59, E32/M57, E38/M57 and E41/M59 were shown to be perspective for genotyping tomato cultivars to select donors of resistance to various stress factors. The clade-specific fragments identified in this work can become the basis for the development of AFLP markers for traits of resistance to stress factors.